2010
DOI: 10.1099/ijs.0.011130-0
|View full text |Cite
|
Sign up to set email alerts
|

Mucilaginibacter rigui sp. nov., isolated from wetland freshwater, and emended description of the genus Mucilaginibacter

Abstract: A non-motile, rod-shaped bacterium, designated strain WPCB133T, was isolated from freshwater collected from the Woopo wetland (Republic of Korea). Cells were Gram-reaction-negative, aerobic and catalase- and oxidase-positive. The major fatty acids were iso-C15 : 0 and anteiso-C15 : 0. The strain contained MK-7 as the major isoprenoid quinone. The DNA G+C content was 47 mol%. A phylogenetic tree based on 16S rRNA gene sequences showed that strain WPCB133T forms an independent lineage within the genus Mucilagini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
57
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 17 publications
6
57
0
1
Order By: Relevance
“…It contains menaquinone-7 (MK-7) as the predominant respiratory quinone and unsaturated and branched saturated fatty acids as the major fatty acids. The G+C content of the genomic DNA of this genus ranges from 42.4 to 47.0 mol% (Pankratov et al, 2007;Urai et al, 2008;Baik et al, 2010). At the time of writing, the genus consisted of 13 validly named species, with M. paludis as the type species (Euzéby, 1997).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It contains menaquinone-7 (MK-7) as the predominant respiratory quinone and unsaturated and branched saturated fatty acids as the major fatty acids. The G+C content of the genomic DNA of this genus ranges from 42.4 to 47.0 mol% (Pankratov et al, 2007;Urai et al, 2008;Baik et al, 2010). At the time of writing, the genus consisted of 13 validly named species, with M. paludis as the type species (Euzéby, 1997).…”
mentioning
confidence: 99%
“…The genus Mucilaginibacter was recently proposed by Pankratov et al (2007) and emended by Urai et al (2008) and Baik et al (2010) in order to accommodate Gram-negative, strictly aerobic or facultatively anaerobic, chemoheterotrophic, rod shaped bacteria. It contains menaquinone-7 (MK-7) as the predominant respiratory quinone and unsaturated and branched saturated fatty acids as the major fatty acids.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… Strains: 1, DR‐f4 T ; 2, Mucilaginibacter lappiensis ANJLI2 T ; and 3, Mucilaginibacter rigui WPCB133 T . Data are from this study, Männistö et al (2010) and Baik et al (2010). All strains are nonmotile rods and positive for catalase, oxidase, alkaline phosphatase, leucine arylamidase, valine arylamidase, acid phosphatase, α‐galactosidase, β‐galactosidase, α‐glucosidase, β‐glucosidase, N ‐acetyl‐β‐glucosaminidase, aesculin hydrolysis, assimilation of d ‐glucose, d ‐mannose, N ‐acetyl‐glucosamine and d ‐maltose, and acid production from d ‐arabinose, d ‐galactose, d ‐glucose, d ‐mannose, d ‐cellobiose, d ‐maltose, d ‐lactose and d ‐melibiose.…”
Section: Resultsmentioning
confidence: 99%
“…The G+C content of strain DR‐f4 T was 42.6 mol%. Baik et al (2010) reported that the G+C content of the genus Mucilaginibacter is between 42.4 and 47 mol%.…”
Section: Resultsmentioning
confidence: 99%